2023
DOI: 10.1177/11795514231155635
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics Analysis of Next Generation Sequencing Data Identifies Molecular Biomarkers Associated With Type 2 Diabetes Mellitus

Abstract: Background: Type 2 diabetes mellitus (T2DM) is the most common metabolic disorder. The aim of the present investigation was to identify gene signature specific to T2DM. Methods: The next generation sequencing (NGS) dataset GSE81608 was retrieved from the gene expression omnibus (GEO) database and analyzed to identify the differentially expressed genes (DEGs) between T2DM and normal controls. Then, Gene Ontology (GO) and pathway enrichment analysis, protein-protein interaction (PPI) network, modules, miRNA (mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 263 publications
(207 reference statements)
0
13
0
Order By: Relevance
“…Therefore, understanding the pathological changes and molecular mechanisms of MS is essential for clinical diagnosis and treatment. Efficient NGS and bioinformatics analyses help us understand the molecular mechanisms of the disease onset and advancement, which is invaluable for biomarkers and therapeutic target identification [5152]. In our study, 959 DEGs were identified between MS patients and normal controls based on NGS dataset.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, understanding the pathological changes and molecular mechanisms of MS is essential for clinical diagnosis and treatment. Efficient NGS and bioinformatics analyses help us understand the molecular mechanisms of the disease onset and advancement, which is invaluable for biomarkers and therapeutic target identification [5152]. In our study, 959 DEGs were identified between MS patients and normal controls based on NGS dataset.…”
Section: Discussionmentioning
confidence: 96%
“…For diagnosis and treatment, it is necessary to further understand the molecular pathogenesis resulting in occurrence and advancement. Due to the advancement of NGS technology, the genetic modifications due to disease progression can be detected, indicating gene targets for diagnosis, therapy and prognosis of specific diseases [38-39].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, next generation sequencing (NGS) technology has been applied to the research on various bioinformatics, which can screen and identify genes and signalizing pathways of various diseases [1920]. NGS is an emerging molecular biology technology based on a high-throughput platform, which is widely used in COPD [21].…”
Section: Introductionmentioning
confidence: 99%